2012
DOI: 10.1007/s00381-012-1912-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolisation of choroid plexus tumours in children: part I—does the reduction of perioperative blood loss affect the safety of subsequent surgery?

Abstract: Our observations with regards to preoperative embolisation of choroid plexus tumours show an acceptable safety profile for the endovascular technique. At the same time, it renders the operative treatment of the tumours safer by reducing perioperative blood loss resulting in a high gross total resection rate. In summary, we suggest that preoperative embolisation is a useful adjunct that should be considered prior to surgical resection in managing these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Even in recent series, only 54% of unembolized CPPs were completely resected. 11 The superior parietal lobule approach has been reported for CPPs of the atrium, 8,17 and in the current series, it provided excellent exposure and afforded vascular control over all tumors, allowing complete resection with minimal blood loss. There are several rationales for this approach over others.…”
Section: B C Kennedy Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…Even in recent series, only 54% of unembolized CPPs were completely resected. 11 The superior parietal lobule approach has been reported for CPPs of the atrium, 8,17 and in the current series, it provided excellent exposure and afforded vascular control over all tumors, allowing complete resection with minimal blood loss. There are several rationales for this approach over others.…”
Section: B C Kennedy Et Almentioning
confidence: 99%
“…6,19,20 It has also been suggested that less intraoperative bleeding due to embolization leads to a higher rate of complete resection and better outcome. 11 However, many series have reported a low rate of successful embolization when attempted due to small tortuous vessels that are difficult or impossible to cannulate, or feeding arteries that are judged to also perfuse deep brain structures. 1,17,20 In addition to these technical difficulties, angiography and embolization are accompanied by small risks of stroke and other complications and should particularly be avoided in the very young because of both deterministic and stochastic long-term radiation effects.…”
Section: B C Kennedy Et Almentioning
confidence: 99%
See 3 more Smart Citations